A rare life-threatening disease: unilateral kidney compressed by huge chronic spontaneous retroperitoneal hemorrhage - Lu HY; Wei W; Chen QW; Meng QG; Hu GH; Yi XL; Bai XZ (Dove Medical Press, 2018)
Hao-Yuan Lu,1,* Wei Wei,2,* Qi-Wei Chen,1,* Qing-Gui Meng,1 Gao-Hua Hu,1 Xian-Lin Yi,1,3 Xian-Zhong Bai1 1Department of Urology, Tumor Hospital of Guangxi Medical University and Guangxi Cancer Research Institute, Nanning 530021, China; 2Department of Radiology, Tumor Hospital of Guangxi Medical University and Guangxi Cancer Research Institute, Nanning 530021,China; 3Hubei Engineering Laboratory for Synthetic Microbiology, Wuhan Institute of Biotechnology, Wuhan 430075, China *These authors contributed equally to this work Objectives: To study an uncommon life-threatening disease, spontaneous retroperitoneal and perirenal hemorrhage. Case descriptions: A 69-year-old male presented with pain in the left waist and back of 1 month duration. The renal abscess was suspected by magnetic resonance imaging before operation. The perirenal hematoma was cleaned by operation. In another case, the patient had a functional solitary left kidney compressed by a huge retroperitoneal mass and uropenia appeared. Results: The first patient died of adult respiratory distress syndrome after surgery. The second patient died of cardiac insufficiency and pulmonary embolism on the second day after evacuation of retroperitoneal hematoma. Conclusion: Conservative surgery, such as selective arterial embolization, is a reasonable approach in patients with chronic spontaneous retroperitoneal and perirenal space hemorrhage and with poor general condition. We strongly recommend drainage or interventional therapy, but not a major surgery, in patients with poor condition. Keywords: kidney, spontaneous, retroperitoneal, hemorrhage, surgery